Genetic diversity analysis of Rose varieties from Grandiflora group based on ISSR molecular markers - Yudanova Sophia S. (EDP Sciences, 2021)
Kinship and genetic diversity determination among six rose varieties from the Grandiflora group were carried out using ISSR thechnics. The studied varities were divided into 3 clades: I) ‘Lezginka’, ‘Queen Elizabeth’ and ‘Koralovy surpriz’ varieties; II) ‘Gurzuf’ and ‘Love’ varieties; III) ‘Komsomolsky ogonek’ variety formed a separate branch. This division into clades was confirmed by a statistical comparison of morphometric characters. On the basis of the obtained data, it can be concluded that the analysis using the selected primer group is well-suited for differentiation rose varieties into groups, which makes it possible, for one thing, to determine the genetic distance between varieties, and for another, to use these data in the future by certification of the varieties promising by resistance characters to the continental climate conditions.